Anarchic Souls in the Leviacene Age - LaMothe, Ryan (Pastoral psychology, 2025)
This article contends that Western iterations of sovereignty and its apparatuses produce, in part, souls and selves that have contributed to destructive, depersonalizing relations between human beings, other species, and the Earth. Given this, it is necessary to reimagine the notion of "soul" in relation to the idea of anarchy with the aim of creating more life-enhancing and inclusive eco-social-political relations. The underlying premise of this article is that anarchic souls are an existential reality that, in the West, have mostly been hidden, denied, or suppressed as a result of persons internalizing the philosophical and theological ideas, beliefs, and values associated with varied apparatuses of domination.